Importancia de los modelos conceptuales y teorías de enfermería: experiencia de la Facultad de Enfermería de la Universidad de La Sabana (2005)
From the early years of the XX century, the discipline of Nursing has had an important development, evidenced in post graduate formation, and in the development of conceptual models and nursing theories, as a product of investigative activity. The article highlights the importance of taking these models and theories into practice, as a strategy to strength disciplinary knowledge, with the corresponding repercussions in terms of quality, autonomy and visibility in nursing care. The experience of the application of the Roy Adaptation Model is presented as a frame of reference of the professional foundation subjects at the Nursing School of Universidad de La Sabana, the steps followed for its implementation and the results obtained.